Development of catalysts and electrolyzers toward industrial-scale CO2 electroreduction. Issue 37 (15th June 2022) - Li, Geng; Liu, Yong; Zhang, Qiang; Hu, Qiushi; Guo, Weihua; Cao, Xiaohu; Dou, Yubing; Cheng, Le; Song, Yun; Su, Jianjun; Huang, Libei; Ye, Ruquan
Abstract : Here we summarize the recent developments of catalysts and electrolyzers for the CO2 reduction reaction, which have improved product selectivity and enabled the delivery of industrial-scale current densities. Abstract : The electrochemical CO2 reduction reaction (CO2 RR) has attracted significant research interest in recent years due to its potential to mitigate carbon emissions while providing valuable fuels and chemicals. The performance of the CO2 RR has been improved from tens of milliamperes per square centimeter to orders of magnitude higher, with selectivity approaching 100% for some products. This review will highlight the key development of the CO2 RR toward industrially relevant performance. We will first discuss the recent advances of electrocatalysts in refining the product's selectivity. A few representative electrocatalysts will be showcased, including metal-free catalysts, metal nanoparticles, and molecular catalysts and their derivatives. Then we will show the development of electrochemical cells for the CO2 RR, which play a pivotal role in achieving a current density of amperes per square centimeter. Specifically, using the flow electrolyzer has significantly improved the CO2 RR current densities compared to the conventional H-type cell. Lastly, we will provide perspectives on future development and challenges of the CO2 RR.